Artificial Intelligence, Transhumanism and the Digital Spirit: Ethical Challenges in the Abrahamic Traditions - Rizky HK, Muhammad (AL-ADYAN, 2026)
Abrahamic religions confront new theological and ethical issues as artificial intelligence (AI) increasingly mediates moral judgments and reconfigures human identity. This article explores the ethical, anthropological, and spiritual implications of AI and transhumanism using a comparative hermeneutic analysis based on Islam, Christianity, and Judaism. Using recent peer-reviewed literature and the writings of Yuval Noah Harari, Paul Ricœur, Karen Armstrong, and Nidhal Guessoum, the study presents AI as a symbolic "digital spirit" that mimics qualities typically associated with divine authority, such as omniscience, judgment, and moral surveillance, rather than just as a technological advancement. The article uses a methodological synthesis of textual interpretation, ethical theory, and digital theology to see how religious traditions understand human agency in a post-human era,. The Concern regarding techno-messianism, the decline of pneumatology, and the disintegration of moral community are raised by the argument that transhumanist purposes reflect eschatological issues. Despite differences in their doctrinal details, research indicates that Abrahamic religions see AI as a test of ethical stewardship rather than a spiritual replacement. For researchers studying religion, ethics, and technology, this study offers a new theological-ethical framework for examining AI's cultural authority and spiritual symbolism.